PENGARUH KEDALAMAN PEMAKANAN TERHADAP KEKASARAN PERMUKAAN MATERIAL BAJA S45C PADA PROSES PEMBUBUTAN - Firdhan Maulana Alhafizh; Muhammad Hasan Albana; Nur Fitria Pujo Leksonowati (Politeknik Negeri Batam, 2026)
Surface quality is a crucial parameter in the machining process and is significantly influenced by the depth of cut. Selecting this parameter directly affects process efficiency and final product quality. This study aims to investigate the effect of depth of cut on the surface roughness of S45C steel during a conventional lathe turning process. The experimental method involved four depth-of-cut settings (0.2 mm, 0.5 mm, 1.0 mm, and 2.0 mm), with cutting speed and spindle rotation held constant. The turning process was performed using an insert tool, and the resulting surface roughness was measured with a surface roughness tester. The results indicated that as the depth of cut increases, surface roughness (Ra, Rq, and Rz) tends to increase. The best surface quality (average Ra 1.291) was achieved at the smallest depth of cut (0.2 mm), whereas the roughest surface (average Ra 2.728) resulted from the largest depth of cut (2.0 mm). This increase in roughness is attributed to higher cutting forces and vibrations during the machining process. Thus, the proper selection of the depth of cut is crucial for achieving optimal surface quality and machining efficiency.